2011
DOI: 10.1002/ajpa.21471
|View full text |Cite
|
Sign up to set email alerts
|

Odontometric sex discrimination in the herculaneum sample (79 AD, Naples, Italy), with application to juveniles

Abstract: Sex determination of subadult skeletal remains with satisfactory accuracy represents one of the most important limitations of archaeological research and forensic practice. Teeth are one of the most durable physical elements of an individual that remain after death, and constitute a potential source of information about the biological sex of that individual. This study was based on the skeletal remains of 117 individuals from the ancient city of Herculaneum (Naples, Italy), victims of the eruption of the nearb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 51 publications
(75 reference statements)
9
35
0
5
Order By: Relevance
“…A comparison between the two sexes showed that the classification accuracy of all functions was higher for males. This result is in agreement with other studies on cervical tooth measurements (Vodanovic et al 2007;Hassett 2011;Viciano et al 2011Viciano et al , 2013Viciano et al , 2015Zorba et al 2011Zorba et al , 2013Mujib et al 2014;Peckmann et al 2015). This means that females have a greater variation in tooth size and can more often be misclassified as male.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A comparison between the two sexes showed that the classification accuracy of all functions was higher for males. This result is in agreement with other studies on cervical tooth measurements (Vodanovic et al 2007;Hassett 2011;Viciano et al 2011Viciano et al , 2013Viciano et al , 2015Zorba et al 2011Zorba et al , 2013Mujib et al 2014;Peckmann et al 2015). This means that females have a greater variation in tooth size and can more often be misclassified as male.…”
Section: Discussionsupporting
confidence: 94%
“…Discriminant function analysis for single tooth measurements also showed that the cervical measurements of the permanent canines and incisors were the most dimorphic teeth providing classification accuracy between 76.9 and 87.9 %. These results were in accordance with previous studies (Alt et al 1998;Starp 1990;Ellendt 1993;Hassett 2011;Viciano et al 2011Viciano et al , 2013Viciano et al , 2015Mujib et al 2014). In addition, it was found that second molar dimensions can be a very effective single variable for sex estimation with a classification accuracy of 83 %.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The correct identification of sex from skeletal remains is one of the main challenges in forensic anthropology and osteoarchaeology. Dental sexual dimorphism has long been acknowledged as a reliable biological feature in this respect, and studies have demonstrated that dental dimensions can be used to accurately assess the sex of skeletal remains in different populations [1][2][3][4][5][17][18][19][20][21][22][23][24]. The present study is one of few reference studies for sex estimation using odontometric data in Iranian archaeological populations [7].…”
Section: Resultsmentioning
confidence: 99%